THE INFLUENCE OF WORKLOAD, ORGANIZATIONAL CLIMATE AND LEADERSHIP STYLE ON WORK MOTIVATION OF EMPLOYEES IN THE COMMUNICATION, INFORMATION, AND STATISTICS OF A SUNGAI PENUH CITY - Askar Jaya; Ely Mardyah; Ganda Saputra; Fajri Fajri; Harpebri Harpebri (SEAN Institute, 2022)
This study aims to see the effect of (1) Workload on employee motivation at the Department of Communication, Information and Statistics of Sungai Penuh City. (2) Organizational Climate on employee motivation in the Office of Communication, Information and Statistics of Sungai Penuh City. (3) Leadership Style on employee motivation in the Department of Communication, Information and Statistics of Sungai Penuh City. (4) Workload, organizational climate and leadership style have a joint effect on employee motivation at the Department of Communication, Information and Statistics of Sungai Penuh City. The population in this study is all employees at the Department of Communication, Information and Statistics of Sungai Penuh City as many as 39 people. And This sampling technique uses a total sampling technique (whole sample), total sampling is a sampling technique where the number of samples is the same as the population (Sugiyono, 2017) The results of this study indicate that (1) Workload has a significant negative effect on employee motivation at the Department of Communication, Information and Statistics of Sungai Penuh City. (2) Organizational Climate provide a positive influence on employee motivation in the Department of Communication, Information and Statistics Sungai Full City. (3) Leadership Style provide a positive influence on employee motivation in the Department of Communication, Information and Statistics Sungai Full City. (4) workload, organizational climate and leadership stylejointly affect the motivation of employees in the Department of Communication, Information and Statistics Sungai Full City.